Implementasi Penegakan Hukum Terhadap Orang Mabuk Untuk Pembangunan Berkelanjutan Ditinjau Dari Hukum Pidana - Maharani, Sabilla Kusuma; Putri, Maria Sylvia; Amina, Frahnaz; Az Zahra, Shabrina Najla; Fauziyyah, Laila; Yuli W, Yuliana (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The application of the law to individuals addicted to alcohol in the context of sustainable development is a significant aspect of the legal system. This paper discusses the legal framework governing the treatment of alcoholics, especially from a criminal law perspective, with the aim of achieving Sustainable Development goals. This analysis covers various legal provisions, policies and practices relating to law enforcement against violations by individuals related to the Sustainable Development goals, especially those related to health and well-being (SDG No. 3) as well as building peaceful and inclusive societies (SDG No. 16). This article also links these issues to provisions in the Criminal Code, especially Article 492 of the Criminal Code. The research method used is normative juridical analysis.